2013
DOI: 10.1128/mbio.00152-13
|View full text |Cite
|
Sign up to set email alerts
|

An Escherichia coli Effector Protein Promotes Host Mutation via Depletion of DNA Mismatch Repair Proteins

Abstract: Enteropathogenic Escherichia coli (EPEC) is an attaching and effacing (A/E) human pathogen that causes diarrhea during acute infection, and it can also sustain asymptomatic colonization. A/E E. coli depletes host cell DNA mismatch repair (MMR) proteins in colonic cell lines and has been detected in colorectal cancer (CRC) patients. However, until now, a direct link between infection and host mutagenesis has not been fully demonstrated. Here we show that the EPEC-secreted effector protein EspF is critical for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 42 publications
(43 reference statements)
3
67
1
Order By: Relevance
“…It has been shown that EPEC infection can cause phenomena such as dramatically enhancing the spontaneous mutation frequency in host cells, inducing mismatch repair (MMR) protein dysfunction and increasing the levels of host reactive oxygen species, which were considered to be symbols of tumorigenesis. These were dependent on EspF's mitochondrial targeting [57]. Although there is no direct evidence for the relationship between infection and colorectal carcinogenesis, our results provide us with a map of candidate targets.…”
Section: Espf May Induce Colitis and Colorectal Carcinogenesis Through mentioning
confidence: 84%
See 1 more Smart Citation
“…It has been shown that EPEC infection can cause phenomena such as dramatically enhancing the spontaneous mutation frequency in host cells, inducing mismatch repair (MMR) protein dysfunction and increasing the levels of host reactive oxygen species, which were considered to be symbols of tumorigenesis. These were dependent on EspF's mitochondrial targeting [57]. Although there is no direct evidence for the relationship between infection and colorectal carcinogenesis, our results provide us with a map of candidate targets.…”
Section: Espf May Induce Colitis and Colorectal Carcinogenesis Through mentioning
confidence: 84%
“…A/E E. coli infected intestinal epithelial cells by injecting toxic proteins, leading to DNA damage in host cells, and, together with the Toll-like receptor signaling pathway, the NF-κB pathway and other cell inflammatory pathways, accelerated the process of cancer [86][87][88]. A/E E. coli can regulate the expression of DNA mismatch repair protein in host cells by post-transcriptional manipulation of EspF protein, causing a decrease in host cell MMR protein levels, EspF entered the host cell, targeting binding to mitochondria, leading to Apc and MMR protein gene mutations [57], and may even activate kras and other oncogenes, leading to changes in intestinal epithelium, causing colitis and even colorectal carcinogenesis. The occurrence of carcinogenesis is a multifactorial outcome, and it is a complex event caused by chronic inflammation and mutagenesis [84].…”
Section: Discussionmentioning
confidence: 99%
“…This method has been proposed as a potential mechanism for E. coli mediated carcinogenesis [57]. The enteropathogenic strain of E. coli (EPEC) has been demonstrated to produce an effector protein (EspF), which is effectively reducing MMR proteins [63]. The mode of action of effector protein EspF on MMR protein was under the influence on EspF mitochondrial targeting and posttranscriptional.…”
Section: Possible Effects Of Mmr Proteins or Its Epigenetic Regulatormentioning
confidence: 99%
“…It invades a broad range of human epithelial cell lines. It is well-studded that EPEC strains of E. coli synthesize diverse types of effector molecules that are capable to altering the cellular DNA repair [63]. The cytosolic localization of E. coli inside to colon cells permits the bacteria to secrete the effector molecules directly into the cytoplasm of host cells, although these bacterial effector molecules must enter in the cell nucleus of host cell to affect cellular processes.…”
Section: Entry Of Intracellular E Coli Effector Molecules In Host Numentioning
confidence: 99%
“…The presence of EPEC in biopsies from colon cancer patients could also be related to this neoplasm; because in vitro infection of colon cancer cell lines with EPEC causes depletion of proteins associated with DNA repair (mismatch repair MMR) such as MLH1 and MSH2, and consequently somatic mutations in the intestinal epithelial cells are produced (59). The mechanism by which EPEC infection induces DNA damage is not clear, but it has suggested that EspF protein is involved (61). EspF is an important effector protein expressed by both EPEC and EHEC (62), which is easily internalized by epithelial cell through the Type III Secretion System (63).…”
Section: Entero Pathogenic Escherichia Coli and Colon Cancermentioning
confidence: 99%